Formas de produção do espaço periférico metropolitano: um estudo sobre São Benedito na região metropolitana de Belo Horizonte - Gustavo Resgala Silva (2011)
This paper aims to deepen the comprehension of the acting instances in the production of the peripheral urban space, in order to emphasize the segregator characteristics of the relation between the real estate dynamics and the action of the State on metropolitan scenery. With this purpose, it was accomplished an effort of comprehensiveanalysis of the urban evolution of São Benedito region in municipality of Santa Luzia, emphasizing the paper that this urban area executed in the metropolization and peripherization process of the Metropolitan Region of Belo Horizonte. This study is divided according three agents that stood out in this space production, as well as the historical period that each one of this factors was most evident. It is highlighted in this context the approach of the political, social and territorial dynamics around the process of implementation, construction and occupation of more than eight thousand habitational units in the region, result of public policies in the 80s. The implantation of the habitational complexes Cristinaand Palmital in the 80s are revealed as a meaningful mark in the formation of this metropolitan periphery and core factor in the recognition of the States paper in the constitution of this area. The standard of urban periphery growing, seen usually as a result of the absence of planning and state ordering like in the case of popular lots approved withoutthe needed provision of infrastructure, of the irregular or clandestine parcels and land invasions is, therefore, in case of effects and great impacts of implementation of the complexes in the region, result of a direct action of the public power. The construction of an approach of the urban growing process of the region of São Benedito aims, thus, tracesubsidies that demonstrate how the State action legitimated the standards of peripherical growing of the metropolis.